Pharmacokinetic Studies of Antisense Oligonucleotides Using MALDI-TOF Mass Spectrometry - Herkt, Markus; Foinquinos, Ariana; Batkai, Sandor; Thum, Thomas; Pich, Andreas (Frontiers in Pharmacology, 2020)
Cardiac diseases are the most frequent causes of death in industrialized countries. Pathological remodeling of the heart muscle is caused by several etiologies such as prolonged hypertension or injuries that can lead to myocardial infarction and in serious cases to the death of the patient. The micro-RNA miR-132 has been identified as a master-switch in the development of cardiac hypertrophy and adverse remodeling. In this study, MALDI-TOF mass spectrometry (MS) was utilized to establish a robust and fast method to sensitively detect and accurately quantify anti-microRNA (antimiR) oligonucleotides in blood plasma. An antimiR oligonucleotide isolation protocol containing an ethanol precipitation step with glycogen as oligonucleotide carrier as well as a robust and reproducible MS-analysis procedure has been established. Proteinase K treatment was crucial for releasing antimiR oligonucleotides from plasma- as well as cellular proteins and reducing background derived from biological matrices. AntimiR oligonucleotide detection was achieved from samples of studies in different animal models such as mouse and pig where locked nucleic acids-(LNA)-modified antimiR oligonucleotides have been used to generate pharmacokinetic data.